Analisis Pengaruh Produk Hilang Awal Proses Terhadap Perhitungan Harga Pokok Produksi pada PT. ABC - Ranteallo, Asrah Tandirerung; Fitrianingsih, Kukuh (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Product loss early in the process is a significant problem that affects the accuracy of calculating the cost of production (HPP) at PT. A B C. This research aims to analyze the influence of lost products in the early stages of the production process on COGS calculations and identify causal factors and effective control strategies. A descriptive qualitative approach was used to explore this issue, with data collected through in-depth interviews, documentation and direct observation at PT production sites. A B C. The results showed that product loss early in the process caused an increase in COGS of 4.09%, mainly due to an increase in raw material and labor costs. The main causes of lost products include machine setting errors, variations in raw material quality, non-compliance with standard operating procedures (SOP), and lack of worker training. Control of lost products is carried out through standardizing machine settings, improving quality control of raw materials, and continuous training for workers. Although these control measures have shown positive results in reducing the number of lost products, ongoing evaluation and adjustment of strategies is needed to increase the effectiveness of lost product management. This research provides a practical contribution by providing PT. ABC deeper insight into the importance of product control is missing for more accurate COGS calculations. Theoretically, this research enriches the production management and cost accounting literature by revealing the specific influence of lost products in the early stages of the process on COGS, as well as providing a basis for further research. These findings are relevant for other companies facing similar challenges in managing lost products in the early stages of production.